UJI AKTIVITAS ANTIOKSIDAN METODE DPPH SENYAWA TURUNAN KALKON 3-(3,4-DIMETOKSIFENIL)-1-(4’-HIDROKSIFENIL)-2-PROPEN-1-ON - Dwi Koko Pratoko; Indah Purnama Sary (Fakultas Kedokteran Gigi Universitas Jember, 2014)
A new chalcone derivate named 3-(3,4-dimethoxyphenyl)-1-(4-hydroxyphenyl)-2-propen-1-one has been synthesized. 4-hydroxyacetophenone and 3,4-dimethoxybenzaldehyde was mixtured to produce this compound by Claisen-Schmidt condensation. IR and 1H-NMR spectra was used to elucidate the compound structure. The purity of the compound was identified by TLC that showed only one spot and a narrow melting point. Thus, this compound was evaluated for the antioxidant activity by DPPH method and the result showed that IC50 is 318,2 ppm, lower than vitamin C as the standard.